The University of Buenos Aires Third World Institute (1973-1974) - Julieta Chinchilla (Íconos)
This work aims to cover the brief experience of the “Manuel Ugarte” Third World Institute, created in 1973 in the University of Buenos Aires. this study’s objective is to shed light on a forgotten experience and, in particular, to understand the circumstances that, during this moment of history, opened conduits of intellectual exchange and the study of social processes in countries that until then had been of little interest within the national university’s programs. Ultimately, it serves to reconstruct an experience that reflects one of the most interesting periods of time with regard to the study and exchange in the university environment among countries of Africa, Asia and Latin America. The impetus of this phenomenon was related to government incentives that served as an overarching approach for intellectual productivity pertaining to these continents.